The seasonal and spatial variability of ammonium uptake in a hilly watershed - Ye, Sheng; Pan, Jiajia; Li, Jiyu; Yu, Tianxue; Ran, Qihua (Frontiers in Earth Science, 2023)
Elevated nutrient loading can cause deleterious impacts on aquatic ecosystems such as eutrophication.Seasonal variability and land use change often lead to varied nutrient uptake from streams. However, the impacts of seasonal and spatial variation on stream nutrient transport within same watershed haven't been fully understood. Here, we conducted nutrient addition experiments using Tracer Additions for Spiraling Curve Characterization (TASCC) approach within the Xiaogang Watershed, Zhejiang Province, China. Six of the experiments were conducted in one stream every other month and eight releases in eight different streams to quantify ammonium uptake kinetics across different seasons and land uses. Our findings suggest that the uptake capability increases with both discharge and ambient concentration (C0): seasonal variability of discharge shown small impacts on uptake metrics, except the ambient uptake length (Sw-amb), which increases with discharge; while the change in C0 could have more significant effects on both ambient areal uptake (Uamb) and maximum areal uptake rate parameter (Umax). Downstream the river network, the increase in discharge led to significant increase in Uamb, ambient uptake velocity (Vf-amb) and Umax. On the other hand, the change in C0 is less influential than discharge along the river network, which may be correlated with the hydraulic geometry. Additionally, there is an optimal temperature (T) for uptake in our study region around 17℃, which may be explained by the growth of chlorophyll a. The positive correlation between Vf-amb and Q at the spatial scale may be attributed to the increase of DOC and river chlorophyll a downstream with stream width. In addition, land use had an important effect on ion concentration in streams, and the proportion of agricultural land was positively correlated with nutrient concentration. Our findings could help provide scientific support for land use management and water quality regulation.